Proangiogenic and Prosurvival Functions of Glucose in Human Mesenchymal Stem Cells upon Transplantation123. (25th February 2013) - Deschepper, Mickael; Manassero, Mathieu; Oudina, Karim; Paquet, Joseph; Monfoulet, Laurent‐Emmanuel; Bensidhoum, Morad; Logeart‐Avramoglou, Delphine; Petite, Herve
Abstract: A major limitation in the development of cellular therapies using human mesenchymal stem cells (hMSCs) is cell survival post‐transplantation. In this study, we challenged the current paradigm of hMSC survival, which assigned a pivotal role to oxygen, by testing the hypothesis that exogenous glucose may be key to hMSC survival. We demonstrated that hMSCs could endure sustained near‐anoxia conditions only in the presence of glucose. In this in vitro cell model, the protein expressions of Hif‐1α and angiogenic factors were upregulated by the presence of glucose. Ectopically implanted tissue constructs supplemented with glucose exhibited four‐ to fivefold higher viability and were more vascularized compared to those without glucose at day 14. These findings provided the first direct in vitro and in vivo demonstration of the proangiogenic and prosurvival functions of glucose in hMSC upon transplantation and identified glucose as an essential component of the ideal scaffold for transplanting stem cells. STEM CELLS 2013;31:526–535